Dual BLyS/APRIL targeted therapy with telitacicept in rituximab-refractory SLE-associated neuromyelitis optica spectrum disorder: a case report - Dai, Mingfen; Huang, Chunyan; Zhou, Mingxuan; Leong, Pui-Ying; Chen, Xiaoqing (Frontiers in Immunology, 2025)
This article presents a case of neuromyelitis optica spectrum disorder (NMOSD) secondary to systemic lupus erythematosus (SLE). The patient initially presented with unexplained nausea, vomiting, intractable hiccups, and significant bradycardia (48 bpm). Cranial and spinal MRI findings were unremarkable, while serum aquaporin-4 immunoglobulin G (AQP4-IgG) antibody titers were markedly elevated (1:320). Following exclusion of alternative etiologies through comprehensive serological and neuroimaging investigations, the diagnosis of area postrema syndrome (APS) was confirmed according to the 2015 International Panel for NMO Diagnosis (IPND) criteria as a distinct NMOSD subtype. The patient exhibited a rapid therapeutic response to high-dose glucocorticoid therapy and was discharged on maintenance methylprednisolone with adjunctive medications. At one-month follow-up, the patient reported progressive visual deterioration, prompting neuro-ophthalmologic evaluation. Clinical findings included mildly elevated intraocular pressure (22.2 mmHg OD, 22.5 mmHg OS), corrected refractive error, and abnormal visual evoked potentials (diminished amplitude with delayed waveforms). Other neuro-ophthalmic investigations revealed no abnormalities. Persistent AQP4-IgG seropositivity (titer 1:32) was noted, and gadolinium-enhanced MRI revealed focal signal abnormalities in the bilateral optic nerves, confirming optic neuritis. Intravenous rituximab therapy (500 mg every two weeks) was initiated; however, treatment was complicated by a generalized urticarial rash and pleuritic chest pain, with no significant improvement in visual acuity. The therapeutic regimen was subsequently modified to incorporate subcutaneous telitacicept (160 mg weekly) in combination with glucocorticoid taper protocol and hydroxychloroquine. After eight weeks of this combined therapy, marked visual improvement was observed. Follow-up gadolinium-enhanced MRI revealed decreased enhancement intensity in the corresponding optic nerve regions compared to baseline. The patient maintained clinical stability and continues long-term multidisciplinary surveillance. To our knowledge, this represents the third documented case validating the therapeutic efficacy of telitacicept in NMOSD. Our findings suggest that telitacicept may serve as a disease-modifying therapy for SLE patients with AQP4-IgG-seropositive NMOSD.